Longitudinal evaluation of the impact of immunosuppressive regimen on immune responses to COVID-19 vaccination in kidney transplant recipients - Wiedemann, Aurélie; Pellaton, Céline; Dekeyser, Manon; Guillaumat, Lydia; Déchenaud, Marie; Krief, Corinne; Lacabaratz, Christine; Grimbert, Philippe; Pantaleo, Giuseppe; Lévy, Yves; Durrbach, Antoine (Frontiers in Medicine, 2022)
Immunocompromised patients have a high risk of death from SARS-CoV-2 infection. Vaccination with an mRNA vaccine may protect these patients against severe COVID-19. Several studies have evaluated the impact of immune-suppressive drug regimens on cellular and humoral responses to SARS-CoV-2 variants of concern in this context. We performed a prospective longitudinal study assessing specific humoral (binding and neutralizing antibodies against spike (S) and T-lymphocyte (cytokine secretion and polyfunctionality) immune responses to anti-COVID-19 vaccination with at least two doses of BNT162b2 mRNA vaccine in stable kidney transplant recipients (KTR) on calcineurin inhibitor (CNI)- or belatacept-based treatment regimens. Fifty-two KTR — 31 receiving CNI and 21 receiving belatacept — were enrolled in this study. After two doses of vaccine, 46.9% of patients developed anti-S IgG. Anti-spike IgG antibodies were produced in only 21.4% of the patients in the belatacept group, versus 83.3% of those in the CNI group. The Beta and Delta variants and, more importantly, the Omicron variant, were less well neutralized than the Wuhan strain. T-cell functions were also much weaker in the belatacept group than in the CNI group. Renal transplant patients have an impaired humoral response to BNT162b2 vaccination. Belatacept-based regimens severely weaken both humoral and cellular vaccine responses. Clinically, careful evaluations of at least binding IgG responses, and prophylactic or post-exposure strategies are strongly recommended for transplant recipients on belatacept-based regimens.